Zebrafish cobll1a regulates lipid homeostasis via the RA signaling pathway - Zeng, Ting; Lv, Jinrui; Liang, Jiaxin; Xie, Binling; Liu, Ling; Tan, Yuanyuan; Zhu, Junwei; Jiang, Jifan; Xie, Huaping (Frontiers in Cell and Developmental Biology, 2024)
Background: The COBLL1 gene has been implicated in human central obesity, fasting insulin levels, type 2 diabetes, and blood lipid profiles. However, its molecular mechanisms remain largely unexplored. Methods: In this study, we established cobll1a mutant lines using the CRISPR/Cas9-mediated gene knockout technique. To further dissect the molecular underpinnings of cobll1a during early development, transcriptome sequencing and bioinformatics analysis was employed. Results: Our study showed that compared to the control, cobll1a−/− zebrafish embryos exhibited impaired development of digestive organs, including the liver, intestine, and pancreas, at 4 days post-fertilization (dpf). Transcriptome sequencing and bioinformatics analysis results showed that in cobll1a knockout group, the expression level of genes in the Retinoic Acid (RA) signaling pathway was affected, and the expression level of lipid metabolism-related genes (fasn, scd, elovl2, elovl6, dgat1a, srebf1 and srebf2) were significantly changed (p < 0.01), leading to increased lipid synthesis and decreased lipid catabolism. The expression level of apolipoprotein genes (apoa1a, apoa1b, apoa2, apoa4a, apoa4b, and apoea) genes were downregulated. Conclusion: Our study suggest that the loss of cobll1a resulted in disrupted RA metabolism, reduced lipoprotein expression, and abnormal lipid transport, therefore contributing to lipid accumulation and deleterious effects on early liver development.